The effects of the invasive seaweed asparagopsis armata on native rock pool communities: evidences from experimental exclusion - Silva, Carla (2021)
Biological invasions represent a threat to ecosystems, through competition and habitat destruction, which may result in significant changes of the invaded community. Asparagopsis armata Harvey 1855 is a red macroalgae (Rodophyta) globally recognized as an invasive species. It is found from the intertidal to shallow subtidal areas, on rock or epiphytic, forming natural vegetation belts on exposed coasts. This study evaluated the variations on native intertidal seaweed and macroinvertebrate assemblages inhabiting rock pools with and without the presence of the invasive macroalgae A. armata. To achieve this, manipulation experiments on Atlantic (Portugal) rock pools were done. Three rock pools were maintained without A. armata by manual removal of macroalgae, and three others were not experimentally manipulated during the study period and A. armata was freely present. In this study the variations between different rock pools were assessed. Results showed different patterns in the macroalgae composition of assemblages but not for the macrobenthic communities. Ellisolandia elongata (J. Ellis & Solander) K.R. Hind & G.W. Saunders 2013 was the main algal species affected by the invasion of A. armata. Invaded pools tended to show less macroalgal species richness, showing a more constant and conservative structure, with lower variation of its taxonomic composition than the pools not containing A. armata, where the variability between samples was always higher. Despite the importance of the achieved results, further data based on observation of long-term series are needed, in order to further understand more severe effects of the invader A. armata on native macroalgal assemblage.